(untitled) (Research, Society and Development, 2020)
Objective: To understand the nursing academic’s perception about the theoretical-practical applicability ofhome visits,theirimpact on the users’ health and the changes that occur in the family context. Method: Acase report developed in the subjectof Public Health Care II of the nursing curriculumat the Federal University of Juiz de Fora, state of Minas Gerais, by its students during the first semestre of 2019 and took place in a primary care unit in the city of Juiz de Fora. Results: Three topics emerged where we can see that nurses must act actively in the process of planning. Conclusion: The research points to the possibility of insertionof new operating models in planning, executing and evaluating home visits implementation and evaluation performance of a home visit in such a way that is efficient and meets the national health system’s principles.